Biology student's Understanding of Nature of Science (NOS) and metacognitive awareness at higher education. (June 2020) - Sukaesih, S; Zubaidah, S; Mahanal, S; Listyorini, D
Abstract: The nature of science (NOS) is a crucial aspect of scientific literacy and also a major goal in science education. To achieve science education goal, students' knowledge and metacognition are highly required. This study described Biology student's understanding of NOS and their metacognition at higher education. This study was a survey of semester-four students. Data on NOS was from the Views of Nature of Science (VNOS) questionnaire form B, and students' metacognition data was from the Metacognitive Awareness Inventory (MAI) questionnaire. Data were analyzed descriptively. The results showed that the average of biology students' NOS understanding is 60.35%. Based on seven aspects of NOS understanding studied, the highest achievement is in the empirical-based science aspect (68.69%), the lowest performance is in the subjective science aspect which is full of theoretical content (49.49%). Students' Metacognitive regulation has a lower average (77.4%) than metacognitive knowledge (81.33%). It is found that Biology student's NOS understanding is still weak, and their metacognition still needs to be fixed. This research suggests that biology student's NOS understanding and metacognitive awareness still needs to be upgraded through the learning process so that students would be scientifically-literate and successful in their higher education.